MINERALOGICAL AND GEOCHEMICAL STUDY OF NEOGENE RED BEDS FROM MOUDANIA AND POTIDEA, CHALKIDIKI (MACEDONIA, GREECE) - Tsirambides, A.; Georgiadis, I. K.; Papadopoulos, A. A.; Ziafetis, A. A.; Giouri, A. N. (Bulletin of the Geological Society of Greece, 2007)
The Neogene red beds from Moudania and Potidea (Chalkidiki) are studied in order to find the conditions under which they were formed. They are incoherent coarse grained sands, with poorly sorted grains. Angular to sub-angular rock fragments derived from the adjacent parent rocL· are very common. The red beds are texturally and mineralogically immature. Most of the samples are gravel sands. The extended presence of sand size grains (>0.063 mm) in the samples suggests high intensity of weathering of the parent rocks and rapid transportation and deposition of the weathered materials close to the source area. The detrital minerals present in the whole samples in decreasing abundance are quartz, feldspars (plagioclase + orthoclase), mica (+clay minerals), pyroxene, amphibole, pyrite and halite (except two samples which are rich in calcite). In the <0.063 mm fraction quartz decreases greatly, while feldspars increase. The presence of illite, smectite (+illite/smectite), and chlorite (+vermiculite) in the <0.063 mm fraction is evident. The most likely source minerals for the formation of the studied red beds are quartz, feldspars, micas, and various Fe-Mg silicates, which are primary constituents of the Mesozoic basement igneous and metamorphic rocks predominating in the adjacent area. In the poorly drained lowland of the studied area mean annual air temperature is 16.2° C, mean annual humidity 75%, and mean annual rainfall 59.5 cm. The samples may be considered ferromagnesian and potassic sandstones. The felsic igneous provenance signature is justified for most of the samples. The climate under which these Neogene red beds were formed was warm and semiarid.